2017
DOI: 10.1016/j.tsf.2017.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotransport properties of La 1−x Ca x MnO 3 (0.52 ≤ x ≤ 0.75): Signature of phase coexistence

Abstract: We report the temperature and magnetic field dependence of transport properties in epitaxial films of the manganite La 1−x Ca x MnO 3 in the overdoped region of the phase diagram for x > 0.5, where a charge-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
2
1
0
Order By: Relevance
“…We focus on the very boundary between the FM metallic and CO/AFM insulating phases x = 0.5, where the grain size is known to have a large impact on the stability of the CO/AFM phase [46][47][48][49][50][51][52]. Our results show the presence of the 3D VRH in accordance with the thin film study [45] and the coexistence of both FM and CO/AFM phases. Reducing the grain size leads to the suppression of the CO/AFM state and a growth of the FM contribution.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…We focus on the very boundary between the FM metallic and CO/AFM insulating phases x = 0.5, where the grain size is known to have a large impact on the stability of the CO/AFM phase [46][47][48][49][50][51][52]. Our results show the presence of the 3D VRH in accordance with the thin film study [45] and the coexistence of both FM and CO/AFM phases. Reducing the grain size leads to the suppression of the CO/AFM state and a growth of the FM contribution.…”
Section: Introductionsupporting
confidence: 80%
“…To gain insight into the origin of the insulating behavior in manganites, we recently focused on the poorly explored insulating CO/AFM part of the phase diagram x > 0.5 (Figure 1a). Our study on La 1−x Ca x MnO 3 thin films indicated that dc resistivity follows the Mott three-dimensional (3D) variable-range-hopping(VRH) mechanism, which implies the crucial role of structural disorder in driving the insulating behavior through the Anderson localization of conducting e g electrons [45]. To further explore these ideas, here we conduct a dc transport and magnetization study on polycrystalline (ceramic) La 1−x Ca x MnO 3 samples, where the level of structural disorder can be controlled by the grain size.…”
Section: Introductionmentioning
confidence: 87%
“…In particular, a negative magnetoresistance has been observed in many materials, see e.g. [39,40,41,42,43,44,45,46]. Interestingly, one finds from Figure 8 that our system also exhibits negative magnetoresistance 11 .…”
Section: Dyonic Solutions and Negative Magnetoresistancesupporting
confidence: 55%
“…As we can see, the La 0.5 Ca 0.5 MnO 3 ceramic sample with the largest grains (4000 nm) shows a clear maximum in dlnρ/dln(1/T) at ≈ 200 K. Such a maximum in dlnρ/dln(1/T) is typical for La 1−x Ca x MnO 3 compounds in the CO/AFM insulating part of phase diagram x ≥ 0.5, and as shown in Refs. [99,100], its position agrees well with the temperature at which the CO transition is expected to occur according to the phase diagram. The maximum in dlnρ/dln(1/T) at ≈ 200 K in Figure 8b shows a fair agreement with the phase diagram as well.…”
Section: La 05 Ca 05 Mnosupporting
confidence: 75%